2012
DOI: 10.1155/2012/892571
|View full text |Cite
|
Sign up to set email alerts
|

On the Solutions of a General System of Difference Equations

Abstract: We deal with the solutions of the systems of the difference equationsxn+1=1/xn-pyn-p,yn+1=xn-pyn-p/xn-qyn-q, andxn+1=1/xn-pyn-pzn-p,yn+1=xn-pyn-pzn-p/xn-qyn-qzn-q,zn+1=xn-qyn-qzn-q/xn-ryn-rzn-r, with a nonzero real numbers initial conditions. Also, the periodicity of the general system ofkvariables will be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…[2]. However, we have found that there is an error in one of the result stated in [17]. Perhaps because the result was not supported by any analytical justifications.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…[2]. However, we have found that there is an error in one of the result stated in [17]. Perhaps because the result was not supported by any analytical justifications.…”
Section: Introductionmentioning
confidence: 80%
“…It is worth mentioning that other related papers also appeared in literature before ours [33], see, for example, Cinar [5] [43]. With our set objective, we shall revisit two recent studies (see [2] and [17]) and present more results regarding the topic discussed in these papers. In the first part of our paper, we consider the system of difference equations (Sys.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations